2019
DOI: 10.1093/europace/euz122
|View full text |Cite
|
Sign up to set email alerts
|

A cellular model of Brugada syndrome with SCN10A variants using human-induced pluripotent stem cell-derived cardiomyocytes

Abstract: Aims Brugada syndrome (BrS) is associated with a pronounced risk to develop sudden cardiac death (SCD). Up to 21% of patients are related to mutations in SCN5A. Studies identified SCN10A as a contributor of BrS. However, the investigation of the human cellular phenotype of BrS in the presence of SCN10A mutations remains lacking. The objective of this study was to establish a cellular model of BrS in presence of SCN10A mutations using human-induced pluripotent stem cell-derived cardiomyocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 20 publications
5
30
0
Order By: Relevance
“…As previously mentioned, one such study demonstrated the similarity in phenotype between patients harboring SCN10A variants, as opposed to SCN5A variants, including personal history of cardiac arrest/syncope, spontaneous BrS electrocardiogram pattern, family history of sudden death, and arrhythmic substrate [77]. This is consistent with functional studies performed in human-induced pluripotent stem cell-derived cardiomyocytes, in which single-cell phenotype features of BrS were seen in cells from a patient harboring the variants NM_006514.3:c.3803G>A and NM_006514.3:c.3749G>A in the SCN10A gene [47]. In a multicenter study in which candidate genes were sequenced, including SCN10A, the study concluded that the common rs6795970 in the SCN10A gene was strongly associated with BrS and resulted in a loss of function of Na V 1.8, as did rare SCN10A variants found in patients, although co-segregation studies did not always support the functional study findings [45].…”
Section: Sodium Channel Mutationssupporting
confidence: 87%
See 1 more Smart Citation
“…As previously mentioned, one such study demonstrated the similarity in phenotype between patients harboring SCN10A variants, as opposed to SCN5A variants, including personal history of cardiac arrest/syncope, spontaneous BrS electrocardiogram pattern, family history of sudden death, and arrhythmic substrate [77]. This is consistent with functional studies performed in human-induced pluripotent stem cell-derived cardiomyocytes, in which single-cell phenotype features of BrS were seen in cells from a patient harboring the variants NM_006514.3:c.3803G>A and NM_006514.3:c.3749G>A in the SCN10A gene [47]. In a multicenter study in which candidate genes were sequenced, including SCN10A, the study concluded that the common rs6795970 in the SCN10A gene was strongly associated with BrS and resulted in a loss of function of Na V 1.8, as did rare SCN10A variants found in patients, although co-segregation studies did not always support the functional study findings [45].…”
Section: Sodium Channel Mutationssupporting
confidence: 87%
“…Therefore, it is necessary to understand both the genes and specific pathogenic variants involved in the pathogenesis of BrS in humans before it will be possible to create animal models using those genetic alterations. Currently, single-cell methods, such as the use of induced pluripotent stem cells, are commonly used to assess the effect of individual variants within particular genes found in patients [47]. However, findings from these studies should be interpreted with caution, since this model is limited by the functional immaturity of the cells [135,136].…”
Section: Discussionmentioning
confidence: 99%
“…To test whether CMs exhibited BrS phenotype, we differentiated heterozygous R1879W-H9 cells into CMs, and electrophysiology was recorded by the LEAP assay ( Figure 5D ). APD50, APD90, and FPDc of R1879W-CMs showed no significant difference compared with WT-CMs ( Figures 5E–H ), consistent with previous studies ( Miller et al, 2017 ; El-Battrawy et al, 2019 ). However, R1879W-CMs exhibited sustained triggered activity ( Figure 5I ), which is a typical characteristic of BrS patient-specific iPSC-derived CMs ( Liang et al, 2016 ).…”
Section: Resultssupporting
confidence: 92%
“…We finally evaluated a novel mutation identified from a BrS patient. Interestingly, this mutation does not influence APD and FPDc but induces sustained triggered beats, consistent with BrS phenotypes at cellular levels when studied previously (Liang et al, 2016;Miller et al, 2017;El-Battrawy et al, 2019). In summary, these data demonstrate the utility of epi-BEs and provide the biomedical research community with a useful tool for diseasing modeling and deciphering novel mutations.…”
Section: Discussionsupporting
confidence: 71%
“…While some studies reported no clear electrophysiological abnormalities in Brugada syndrome patient-derived iPSC-derived cardiomyocyte lines compared to controls [ 147 , 148 ], other reports contrarily showed evidence of significant alterations in action potential duration [ 65 , 144 ], decreased I Na density [ 65 , 144 , 145 , 149 , 150 , 151 ], decreased action potential upstroke velocity [ 65 , 144 , 145 , 150 , 151 ], or irregular calcium handling [ 65 , 145 ]. Ma and colleagues found that pacing at a frequency of 0.1 Hz led to a small subgroup (25%) of Brugada syndrome patient-derived iPSC-derived cardiomyocytes presenting with action potentials which were by the authors claimed to resemble the loss of action potential dome configuration as postulated by the repolarization hypothesis, albeit the pacing frequency exceeding human physiological range [ 71 , 144 ].…”
Section: Towards a Molecular Understanding Of Brugada Syndromementioning
confidence: 99%